FDI and economic growth in the GCC: does the oil sector matter? - Elheddad, Mohamed; Bassim, Mohga; Ahmed, Rizwan (Economics and Business Letters, 2021)
This paper investigates the impact of sectoral foreign direct investment (FDI) on economic growth by validating the resource curse hypothesis in the Gulf Cooperation Council (GCC) countries. Applying OLS (Fixed and Random effects), Instrumental Variables (IV) and Limited Information Maximum Likelihood (LIML) estimations, empirical results indicate that resource-FDI inflows hinder economic growth in the GCC economies, while non-resource FDI has an insignificant effect on growth. Moreover, the total Greenfield FDI inflows deter economic growth in GCC economies. These results give evidence on the crowding-out effect of resource-FDI. This paper opens new insights for policymakers in designing a comprehensive policy on direct FDI inflows (resource and non-resource) for attaining sustainable economic development for the long run.